Metagenomic sequencing combined with flow cytometry facilitated a novel microbial risk assessment framework for bacterial pathogens in municipal wastewater without cultivation. Issue 1 (5th January 2023) - Fu, Songzhe; Wang, Rui; Xu, Zheng; Zhou, Huiwen; Qiu, Zhiguang; Shen, Lixin; Yang, Qian
Abstract : A workflow that combined metagenomic sequencing with flow cytometry was developed. The absolute abundance of pathogens was accurately estimated in mock communities and real samples. Metagenome‐assembled genomes binned from metagenomic data set is robust in phylogenetic analysis and virulence profiling.